2020
DOI: 10.1155/2020/5016327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Associated Risk Factors among a Group of Prisoners in the Yaoundé Central Prison

Abstract: Background. Diabetes is a public health problem worldwide, associated with increased morbidity and mortality. According to the International Diabetes Federation (IDF) 2017 data, around 425 million people worldwide suffer from diabetes. This number is expected to increase to 629 million in 2045. Various occidental studies reported the increased prevalence and lower control of diabetes among prisoners. However, there is no data on the characteristics of inmates with diabetes in sub-Saharan Africa. Methods. A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…Thus, prisoners may receive much less impact from networks and media during the epidemic. Moreover, the sedentary lifestyle is reported to threaten prisoners' health because prisoners usually spend much more time indoors than non-prisoners ( 42 ). These conditions may make the prisoners' responses to the window views different from those of the general public.…”
Section: Conceptual Framework Of Exposure-response Pathwaysmentioning
confidence: 99%
“…Thus, prisoners may receive much less impact from networks and media during the epidemic. Moreover, the sedentary lifestyle is reported to threaten prisoners' health because prisoners usually spend much more time indoors than non-prisoners ( 42 ). These conditions may make the prisoners' responses to the window views different from those of the general public.…”
Section: Conceptual Framework Of Exposure-response Pathwaysmentioning
confidence: 99%
“…Psychiatric and digestive pathologies are the health problems that affect inmates most commonly [4]. An increased risk of diet-related diseases, e.g., overweight [5,6], obesity [5,6], diabetes [7][8][9], atherosclerosis [8,10], and arterial hypertension [4,8,10], is observed as well. The development of this type of disorder 2 of 14 is promoted by many other factors that are not directly related to physical inactivity or inadequate nutrition, e.g., primarily drug use, alcohol abuse, and smoking [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent research has shown that people living in prison in Western countries tend to develop mental illnesses and reduced psychological well-being, diseases in which physical activity has proven to have beneficial effects [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%